PERANAN STATISTIKA DALAM PENELITIAN PENDIDIKAN MATEMATIKA - Syafrida Hanum Hutasuhut (MES: Journal of Mathematics Education and Science, 2022)
Research is an activity to obtain a solution to a problem or phenomenon that occurs through scientific steps. To understand research, researchers must first understand what statistics are. Statistics is a science that studies the methods of collecting, processing, interpreting and drawing conclusions from the data collected or obtained. Therefore, statistics is said to be one of the sciences that is indispensable in research, not least in the field of mathematics education because statistics are used to identify and describe the relationships obtained from the data that has been collected and then processed to obtain a conclusion. The role of statistics has been seen from before the research was carried out, the research took place until the processing of research results.